Group Differences in the Mutual Gaze of Chimpanzees (Pan Troglodytes) - Bard, Kim A; Myowa-Yamakoshi, Masako; Tomonaga, Masaki; Tanaka, Masayuki; Costall, Alan; Matsuzawa, Tetsuro (Developmental psychology, 2005)
A comparative developmental framework was used to determine whether mutual gaze is unique to humans and, if not, whether common mechanisms support the development of mutual gaze in chimpanzees and humans. Mother-infant chimpanzees engaged in approximately 17 instances of mutual gaze per hour. Mutual gaze occurred in positive, nonagonistic contexts. Mother-infant chimpanzees at a Japanese center exhibited significantly more mutual gaze than those at a center in the United States. Cradling and motor stimulation varied across groups. Time spent cradling infants was inversely related to mutual gaze. It is suggested that in primates, mutual engagement is supported via an interchangeability of tactile and visual modalities. The importance of mutual gaze is best understood within a perspective that embraces both cross-species and cross-cultural data.